The Effectiveness of the Character-Building Program on the Dimension of Religious Moral in Students (Case Study of SMP Muhammadiyah 1 Prambanan) - Artanto, Dicky; utri, Anggraita Febriana P (Proceeding International Conference on Religion, Science and Education, 2024)
This study aims to: (1) determine character building efforts at SMP Muhammadiyah 1 Prambanan; (2) knowing the programs rolled out by the school to improve the character of students; (3) knowing the effectiveness of character building programs to improve the quality of student character. Data analysis is carried out interactively using the Miles and Huberman method which includes data collection, data presentation, data reduction, and conclusions. The results of this study show that the program that has been rolled out by SMP Muhammadiyah 1 Prambanan in character building for students has been implemented within one and a half years with the result that there are still some students who do not understand the meaning of the character building program rolled out by the school. This is reinforced by the findings of interviews with several students who admitted that they had not carried out the recommended worship activities that should be carried out as a result of the construction of character building programs rolled out by the school. In addition, from the observations of researchers in the daily lives of students, there are also still some students who deliberately and secretly do not participate in worship activities at school. So that the cultivation of the essence of the character building program must be internalized in individual students to foster awareness of charisma in everyday life.